A study the decision making towards government’s servant on buying Takaful (Islamic insurance) / Siti Zawiyah Shuib and Nur Amirah Mohd Nazri - Shuib, Siti Zawiyah; Mohd Nazri, Nur Amirah (2013)
This research is conducting focused to study the decision making towards government’s servants on buying Islamic Insurance (Takaful). Takaful is Islamic Insurance provided by company that is based on Syariah Compliances. To observe this research, there are fourth factors that influencing the decision making toward government servants on buying Takaful which are the level of awareness, promotion, characteristics product and services and also religiosity. The purpose or objective of this study is (1) to identify the level of decision making towards government’s servant on purchase Takaful policy (2) to find the most influence factor that contribute to the government’s servant decision making to purchase takaful insurance policy and (3) to examine the significant relationship between independant and dependant variables. The respondents are from government’s servant area Ayer Keroh, Malacca. 100 questionnaires had been distributed among them. The researcher had used convenience technique which is sampling technique. This researcher was done through the finding by using realibilty test, frequency distribution and descritive analysis. The result show that decision making towards government’s servant on buying Islamic Insurance (Takaful) is high. Even though the level of decision making on buying Takaful among government’s servant is high, but Takaful company still must make an improvement on promotion, level of awareness based on religiosity and introduce the product charactreistic more deeper. Takaful operator must maintained on sales promotion.